ASESMEN AUTENTIK DI PAUD: MENGUNGKAP PEMAHAMAN GURU UNTUK MENDUKUNG PERKEMBANGAN ANAK YANG OPTIMAL - Astri Chintya Astana; Tisya Permatasari (Al-ATHFAL: Jurnal Pendidikan Anak, 2025)
This research is going to describe the understanding of education for early childhood's teachers regading the authentic assesment, with the special focus in the observation technique of the daily learning practice. The method that is used is descriptive quantitative, which encourage the 50% of the active education for early chilhood teacher's and having the experience in the stay in 1 year. The results show that most teachers have a good understanding of the technical aspects of implementing authentic assessment, especially observation techniques (average score 3.62), but their understanding of the basic concepts of authentic assessment still needs improvement (average score 2.84). These findings enhance the importance of ongoing training that balances technical and conceptual aspects to support optimal implementation of authentic assessment in early childhood learning. This study provides an important contribution as a basis for developing training strategies and improving teacher competence to enhance the overall quality of early childhood education. Keywords:  Assessment; Authenticity; Understanding; Teacher; Early Childhood Education